Prevalence and Distribution of Denture Induced Oral Mucosal Lesions among patients Managed In Lahore Teaching Hospital - Syed Hammad Azeem Rizvi, Rummana Aqeel, Afsheen Zaki, Summiya Ijaz, Sofia Syed, Nimra Nadeem (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Oral mucosal lesions commonly develop in denture wearers and are abnormal changes in mucosal colour, texture, ulceration, edema and hyperplasia. They greatly affect the quality of a patient’s life as they have impact on swallowing, speech and mastication with symptoms of burning, pain and irritation. Aim: To find out prevalence, pattern and distribution of most commonly observed oral mucosal lesions in patients wearing removable dentures and their association with age, gender, denture age, nocturnal use and denture hygiene habits. Study design: A cross sectional; observational study Place and duration: Lahore Medical and Dental College from3rd April till3rd July 2021. Methodology: Hundred partially and completely edentulous patients of both genders were included in the study. The age ranged of the patients was between 30 to 80 years. It was a cross sectional observational study. Non probability purposive sampling was used to select the patients. Patient wearing complete or partial dentures in both arches or single arch for at least three months were included. The clinical examination was carried out and depending on clinical appearance of mucosa the diagnosis of denture induced mucosal lesions was made i.e., denture stomatitis, traumatic ulcers and hyperplasia Results: Out of 100 patients 40.0% had no mucosal lesions associated with dentures whereas 60% patients presented with lesions. Out of all the lesions the most frequently reported lesion was the traumatic ulcer 45%, followed by denture induced hyperplasia 10%. Denture stomatitis was 3% and angular cheilitis was least reported in our patients 2%. 36% patients clean their dentures regularly and 64% patients do not clean their dentures or being irregular, Night wearing of the prosthesis was found in 54% patients whereas 46% never wore dentures while sleeping. Conclusion: The prevalence of oral mucosal lesions with complete or partial removable dentures were 60% reported in our patients and traumatic ulcers were the frequently observed lesion. Furthermore, significant association of all lesions with factors like patient’s age, duration of denture use, nocturnal wearing and denture hygiene was found.